Kubernetes : a complete DevOps cookbook : build and manage your applications, orchestrate containers, and deploy cloud-native services /: a complete DevOps cookbook : build and manage your applications, orchestrate containers, and deploy cloud-native services. (2020) - Karslioglu, Murat
No abstract available